Acute Myocardial Infarction in a Patient With Elevated ST-Segment in aVR Lead and Diffuse ST Segment Depression in Other Leads: A Case Report - Safi, Morteza; Khaheshi, Isa; Memaryan, Mehdi (International Journal of Cardiovascular Practice, 2016)
ST elevation in aVR in conjunction with diffuse ST depression in precordial leads may indicate occlusion of very proximal portion of the left anterior descending artery. We present a 54-year old man, with crushing retrosternal pain and ST-segment elevation only in aVR lead and diffuse ST-segment depression in inferior, lateral and precordial leads. The patient was scheduled for emergent coronary angiography, which showed that left anterior descending (LAD) artery was cut off at very proximal portion and urgent CABG was performed for the patient.